Organizational Structure, Duties, Functions, and Service Implementation of the Regional Technical Implementation Unit (UPTD) Rumoh Sejahtera Aneuk Nanggroe (RSAN) under the Aceh Social Service - Rivai Ahmad; Akhyar; Badruzzaman; Zamzami; Teuku Muhammad Zulffikar (Contemporary Public Administration Review, 2026)
Street children remain a social group requiring continuous government intervention and appropriate institutional support. The implementation of services for street children depends not only on formal policies but also on organizational structure, distribution of authority, human resources, and coordination mechanisms. This study aims to analyze the position, organizational structure, duties, functions, and work procedures of the Regional Technical Implementation Unit (UPTD) Rumoh Sejahtera Aneuk Nanggroe (RSAN) under the Aceh Social Service and to examine the implementation of coordination, care, and protection activities. This study employed a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation. The informants consisted of officials within UPTD RSAN involved in the implementation of its duties and functions. Data were analyzed using the interactive model of data condensation, data presentation, and conclusion drawing. The findings indicate that the implementation of the UPTD's organizational position and structure is constrained by limited authority and dependence on the Aceh Social Service in strategic and operational decision-making. The implementation of duties and functions is also affected by limited human resources and an imbalance between personnel and workload. Coordination activities face bureaucratic constraints and limited organizational authority, resulting in less flexible decision-making. Meanwhile, care and protection activities are constrained by the limited number and capacity of caregivers in relation to the number and needs of children served. The study concludes that the effectiveness of UPTD RSAN requires adequate human resources, more effective coordination mechanisms, and improved administrative procedures while maintaining accountability to the Aceh Social Service.